671 Examining Degenerative Disease Adjacent to Lumbosacral Transitional Vertebrae: A Retrospective Cohort Study. (April 2023) - Desai, Ansh; McGrath, Kyle; Schmidt, Eric; Lee, Jonathan; Statsevych, Volodymyr; Steinmetz, Michael P.
Abstract : INTRODUCTION: Bertolotti syndrome is a clinical diagnosis given to patients with lower back pain arising from a lumbosacral transitional vertebra (LSTV). LSTVs cause altered biomechanics at the lumbosacral junction and adjacent segments, predisposing these patients to degenerative disease. Signs of degenerative disease can manifest on magnetic resonance imaging (MRI) as signal changes in the intervertebral discs and facet joints, as well as spinal stenosis and spondylolisthesis, all of which may contribute to a patient's symptoms. METHODS: This is a retrospective analysis of patients with Bertolotti syndrome and anatomically normal controls who received care at a single institution between 2010 and 2020. The control group consisted of patients presenting with lower back pain without an LSTV. Patients with a history of prior trauma, laminectomy, or fusion were excluded. Degree of spinal stenosis and spondylolisthesis, as well as signs of degenerative changes in the intervertebral disc and facet joints, were assessed using sagittal and axial magnetic resonance grading criteria established in prior literature. RESULTS: A total of 173 patients were included in the study, 104 with Bertolotti syndrome and 69 controls. On two-tailed t-test, mean L4-L5 spinal stenosis grade was shown to be significantly different between patients with Bertolotti syndrome (1.00) and control patients (1.47) (p = .002). The difference in mean L4-L5 facet grade (p = .32), mean L4-L5 spondylolisthesis grade (p = .13), and mean L4-L5 disk grade (p=.33) were not significantly different on two-tailed t-test (p = .32). CONCLUSIONS: Patients with Bertolotti Syndrome may be more likely to develop spinal stenosis above the lumbosacral junction than patients without an LSTV. More research needs to be done to determine whether Bertolotti Syndrome patients are at an increased risk to develop clinically-significant lumbar spondylosis.